2016
DOI: 10.1002/jsfa.7622
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and antioxidant activity of polyphenolic extracts fromLactuca sativa(var.Maravilla de Verano) under different farming methods

Abstract: Our data showed the anti-inflammatory and antioxidant potential of Maravilla de Verano polyphenolic extracts. The effect of farming methods on polyphenolic levels was highlighted. The higher reduction of inflammatory mediators release in extracts from plants cultivated under mineral fertilisation treatment was correlated to the higher amount of quercetin. These results can be useful for both nutraceutical or agronomic purposes. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…The slides were then washed with PBS for three times and fluorescein-conjugated secondary antibody (FITC) was added for 1 h, DAPI was used for counterstaining of nuclei. Coverslips were finally mounted in mounting medium and fluorescent images were taken under the Laser Confocal Microscope (Leica TCS SP5, Wetzlar, Germany) [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The slides were then washed with PBS for three times and fluorescein-conjugated secondary antibody (FITC) was added for 1 h, DAPI was used for counterstaining of nuclei. Coverslips were finally mounted in mounting medium and fluorescent images were taken under the Laser Confocal Microscope (Leica TCS SP5, Wetzlar, Germany) [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Anti-iNOS, anti-COX-2, anti-HO-1 and anti-nitrotyrosine (Millipore) were then added for further 30 min. The secondary antibody was added in Fix solution and cells fluorescence was evaluated using a fluorescence-activated cell sorting (FACSscan; Becton Dickinson) and elaborated with Cell Quest software as previously reported [ 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…The radical scavenging activities of Hh-A and trans-tiliroside were assayed using the probe 2′,7′-dichlorofluorescin (DCF) diacetate (H 2 DCF-DA) [40]. H 2 DCF-DA is a non-fluorescent permeant molecule that passively diffuses into cells, where the acetates are cleaved by intracellular esterases to form H 2 DCF and thereby traps it within the cell.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Polyphenols can prevent cancer and cardiovascular diseases (Manach et al, 2004;Hooper and Cassidy, 2006). Adesso et al (2016) reported that lettuce leaf extracts could reduce both the inflammatory and oxidative stress in murine monocyte-macrophage cells by decreasing reactive oxygen species and nitric oxide release. In this sense, quercetin seems to play an important role, and it is probably responsible for antioxidant and anti-inflammatory properties.…”
mentioning
confidence: 99%